Intratracheal Surfactant Administration Attenuates Hyperoxia-Induced Lung Injury and Fibrosis in Neonatal Rats - Jiunn-Song Jiang; Chi-Chun Hsieh; Hsiu-Chu Chou; Chung-Ming Chen (Pediatric Respirology and Critical Care Medicine)
Background: Hyperoxia decreases surfactant production and suggests exogenous surfactant may be a potential treatment for hyperoxia-induced lung injury. This study aimed to investigate the effects of an animal-derived surfactant on hyperoxia-induced lung injury and fibrosis in newborn rats.